THE CORRELATION BETWEEN VOCABULARY MASTERY AND DESCRIPTIVE TEXT WRITING SKILL OF THE TENTH-GRADE STUDENTS OF SMAN 1 KUTA SELATAN IN ACADEMIC YEAR 2021/2022 - Ni Komang Cahyani Dewi; Ni Made Wersi Murtini; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2022)
This study dealt with the correlation between vocabulary mastery and descriptive text writing skill of the tenth-grade students of SMAN 1 Kuta Selatan in academic year 2021/2022. It made used of an ex post facto research design. There were 32 students who were chosen as the samples which was chosen by means of cluster random sampling technique with lottery system. The researcher used two research instruments such as: cloze test for the vocabulary mastery and written descriptive text for the writing skill. The technique of analyzing data were descriptive statistics and inferential analysis using SPSS 16.0. The data were analyzed by using Pearson-Product Moment and t-test. The data of homogeneity was 0.329 and the data of normality of vocabulary mastery was 0.27 while writing skill was 0.55. Furthermore, it was found that the correlation coefficient obtained is 0.781. It shows that there is significant correlation between vocabulary mastery and descriptive text writing skill.